Minisuperspace Quantum Cosmology in Metric and Affine Theories of Gravity - Salvatore Capozziello; Francesco Bajardi (Universe, 2022)
Minisuperspace Quantum Cosmology is an approach by which it is possible to infer initial conditions for dynamical systems which can suitably represent observable and non-observable universes. Here we discuss theories of gravity which, from various points of view, extend Einstein’s General Relativity. Specifically, the Hamiltonian formalism for <semantics>f(R)</semantics>, <semantics>f(T)</semantics>, and <semantics>f(G)</semantics> gravity, with R, T, and <semantics>G</semantics> being the curvature, torsion and Gauss–Bonnet scalars, respectively, is developed starting from the Arnowitt–Deser–Misner approach. The Minisuperspace Quantum Cosmology is derived for all these models and cosmological solutions are obtained thanks to the existence of Noether symmetries. The Hartle criterion allows the interpretation of solutions in view of observable universes.